Auditory Temporal Resolution in Individuals with Diabetes Mellitus Type 2 - Mishra,Rajkishor (2016)
Abstract Introduction "Diabetes mellitus is a group of metabolic disorders characterized by elevated blood sugar and abnormalities in insulin secretion and action" ( American Diabetes Association). Previous literature has reported connection between diabetes mellitus and hearing impairment. There is a dearth of literature on auditory temporal resolution ability in individuals with diabetes mellitus type 2. Objective The main objective of the present study was to assess auditory temporal resolution ability through GDT (Gap Detection Threshold) in individuals with diabetes mellitus type 2 with high frequency hearing loss. Methods Fifteen subjects with diabetes mellitus type 2 with high frequency hearing loss in the age range of 30 to 40 years participated in the study as the experimental group. Fifteen age-matched non-diabetic individuals with normal hearing served as the control group. We administered the Gap Detection Threshold (GDT) test to all participants to assess their temporal resolution ability. Result We used the independent t-test to compare between groups. Results showed that the diabetic group (experimental) performed significantly poorer compared with the non-diabetic group ( control ). Conclusion It is possible to conclude that widening of auditory filters and changes in the central auditory nervous system contributed to poorer performance for temporal resolution task (Gap Detection Threshold) in individuals with diabetes mellitus type 2. Findings of the present study revealed the deteriorating effect of diabetes mellitus type 2 at the central auditory processing level.